P38 Immune checkpoint inhibitor-induced colitis is mediated by CXCR6+ polyfunctional lymphocytes and dependent on IL23/IFNg axis. (19th June 2022) - Lo, Jonathan; Cozzetto, Domenico; Liu, Zhigang; Ibraheim, Hajir; Sieh, Jillian; Olbei, Marton; Alexander, James; Blanco, Jesus Miguens; Madgwick, Matthew; Kudo, Hiromi; Seoane, Rocio Castro; Goldin, Robert; et al.
Abstract : Background and Aims: Immune checkpoint inhibitors (CPI) have revolutionised cancer treatment, with previously untreatable disease now amenable to potential cure. Combination regimens of anti-CTLA4 and anti-PD-1 show enhanced efficacy but are prone to off target immune-mediated tissue injury, particularly at the barrier surfaces. CPI-induced colitis is a common a serious complication. Methods: To probe the impact of immune checkpoints on intestinal homeostasis mice were challenged with combination anti-CTLA4 and anti-PD-1 immunotherapy, manipulation of the intestinal microbiota and antibody blockade/depletion studies. Colonic immune responses were profiled using RNA-sequencing, including high-resolution single cell analyses, and flow cytometry. Results: CPI-colitis was dependent on the composition of the intestinal microbiota and was characterized by remodelling of mucosal lymphocytes with induction of polyfunctional lymphocyte responses characterized by increased expression of interferon-γ (IFNγ), other pro-inflammatory cytokines/chemokines ( Il22, Il17a Ccl3, Ccl4 and Ccl9 ), cytotoxicity molecules ( Gzmb, Gzma, Prf1, Nkg7 ) and the chemokine receptor Cxcr6 . In comparison with mucosal lymphocytes in the steady state, polyfunctional lymphocytes from both CD4 + and CD8 + lineages upregulated costimulatory molecules and checkpoint molecules in CPI-colitis, indicating that these cells are tightly regulated. CPI-colitis was attenuated following depletion of effector lymphocytes or following blockade of the IL23/IFNγ axis. Conclusions: This study provides new mechanistic insights into CPI-colitis, identifying polyfunctional, cytotoxic lymphocytes as key mediators of disease. Therapeutic targeting of their effector response or regulatory networks, including the IL23/IFNγ axis holds the key to preventing and reversing CPI-colitis.